Leading an Assessment Reform: Ensuring a Whole-School Approach for Decision-Making - Alonzo, Dennis; Leverett, Jade; Obsioma, Elisha (Frontiers in Education, 2021)
The ability of teachers to use assessment data to inform decisions related to learning and teaching defines teaching effectiveness. However, to maximise the benefits of teacher decision-making, there is a need to ensure that all teachers across the school are supported to engage in a whole-school approach to ensuring that all students across different stages are supported. This paper reports on a case study of a school in building an assessment culture with a strong focus on using a range of data for teacher decision-making. We used an auto-ethnography to reflect on our experiences in leading this assessment reform. Using the lens of activity theory, we have identified structural, organisational, social and behavioral factors that contribute to the success of the program.